Implementasi Business Licensing Coaching and Socialization Officer (BLCSO) di DPMPTSP Kota Surabaya - Ramadhan, Andhika; Widiyarta, Agus (Universitas Serang Raya, 2024)
Surabaya City is one of the cities that provides good quality public services. The Surabaya City Government through the Business Licensing Coaching and Socialization Officer (BLCSO) at the Surabaya City Investment and One Stop Integrated Service Office, provides assistance and socialization related to Business Licensing and Non-Licensing Services for Micro, Small and Medium Enterprises (MSMEs). This activity is carried out to encourage all business actors to have a Business License Number (NIB) as a form of business legality. The purpose of this research is to find out the role and facilities of BLCSO towards business actors in making NIB for MSMEs in Surabaya City. This research was conducted using descriptive qualitative method with data collection through field observation, interviews, and documentation. After that, a SWOT analysis was carried out to improve services. The results of this study indicate that the quality of public services through BLCSO at the DPMPTSP of Surabaya City has been running well. This is evidenced by the 5 dimensions of public service quality, namely tangibles, reliability, responsiveness, assurance, and empathy. Therefore, BLCSO is a strategic platform in facilitating and improving the effectiveness of the business licensing process.